IMPLEMENTASI MODEL BERGERAK DAN MEDIA BLOOKET UNTUK MENINGKATKAN KETERAMPILAN BERPIKIR KRITIS SISWA - Elisa Fitrida Hidayati; Diani Ayu Pratiwi (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2024)
The research problem is the low activity and critical thinking skills of students in mathematics. The causes are one-way learning, lack of student activeness during learning, not using more innovative learning models and media, and students have not mastered critical thinking indicators. One of these efforts is through the use of the BERGERAK model and Blooket media. The purpose of this study was to improve students' critical thinking skills. This research uses the type of Classroom Action Research (PTK). The research subjects were 20 fifth grade students of SDN Melayu 2. The types of data in this study are qualitative data and quantitative data. The results showed that students' critical thinking skills at meetings 1 to 4 increased from 45% with the criteria "some students are skilled" to 85% with the criteria "almost all students are very skilled". It can be concluded that the BERGERAK model can improve students' critical thinking skills.